The eco-labeling on sustainable roof materials - Hamzani, Norfatiha (2008)
Construction industry is a major sector that needed the consideration of sustainable development agenda through sustainable construction. The sustainable construction therefore has several approaches on eco-friendly building, which focuses on harmony environment. These can be applied through the choices of material and construction methods that resulted in low level of environmental impacts worksites. The sustainable construction agenda involves optimal management of energy, water, waste management, maintenance and comfort improvements such as thermal and acoustic performance, visual and odour aspects through having good quality living. This research therefore is aim to classify sustainable characteristics or eco-friendly elements that can be utilised onto eco-labeling of roof materials through develop the assessment checklist guideline. This research therefore is focusing on roof materials of steep slope roof system that suitable with the tropical Malaysian climate. The data was gathered using the matrix checklist of sustainable characteristics for roof materials. The data then after was analysed using content analysis method and statistical analysis. This study found Clay Tiles, Fiberglass Insulation, Steel Roof Truss, Fiberglass Roofing Tissues and Aluminium drainage materials were the most sustainable roof materials that suited for a steep slope roof system. The simplified matrix checklist of sustainable roof materials then after is produced as the final result of this study that may benefit for construction industry references.